The Role of Internship Program and Entrepreneurship Training to Hole Entrepreneur Capability and Startup Performance - Febrianti, Bella; Kussudyarsana, Kussudyarsana; Setyawan, Anton Agus; Sholahuddin, Muhammad; Maimun, Muhammad Halim (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: This study aims to determine whether entrepreneurial capability mediates the association between an internship, entrepreneurship training, networking learning, and startup performance.Design/Methodology/Approach: This research design is quantitative. The population in this exploration totaled 869 UMS Independent Entrepreneurial Students. Purposive sampling was the sampling method used. The sample size of this study was 250 respondents. Utilizing SMARTPLS software, the Partial Least Square (PLS) was employed to analyze the data in this study.Research findings: Internships, entrepreneurship training, and networking learning had a significant positive effect on startup performance by fostering a portion of their entrepreneurial capabilities.Theoretical contribution/Originality: This research contributes to the field of entrepreneurship in startup companies. In addition, it provides insight into the millennial generation's entrepreneurship to motivate them to become young entrepreneurs. This research also discusses corporate entrepreneurship.Practitioners/Policy implications: Companies need to know what factors affect startup performance so that they can make policies based on the existing conditions for the creation of quality startup companies.Research limitations/Implications: Based on the research done and the research results obtained, several limitations to the research exist. The questionnaire in this study was closed so that each respondent only answered the answer criteria provided. It could allow each respondent to answer the questionnaire, not by the actual situation. Also, the respondents in this study were only limited according to the level of respondents who were within the sample criteria. In this study, it was only limited to the independent and mediating variables. As for other factors that might affect startup performance, they were not examined.